Miracles, demons and spiritual warfare an urgent call for discernment - Gross, Edward N. (Grand Rapids, MI Baker, 1990)
Includes bibliographical references.
Keywords: Miracles; Apologetics -- 20th century; Gifts, spiritual; Demonology